Utilizating Platform Quranic Arabic Corpus For Arabic Linguistic Education Based Quranic Grammar - Karimah, Lina Husnul; Yurianto, Ramdhan; aliah, mujahidatul; Putri, Dellira (Al-Manar, 2025)
The digital era is an era where all information matters can be accessed through digital media. Many digital platforms that can be used to support even the main platform in learning are no exception for Arabic learning platforms. One of the Arabic learning platforms that can be used for the field of linguistics is the Quranic Arabic Corpus Platform. But it is very unfortunate because there are still very few students, Arabic teachers, and also Arabic lecturers who still apply the Quranic Arabic Corpus platform in their teaching. Even though this platform has very many benefits and conveniences that can be obtained by students and lecturers. Research is a descriptive qualitative research literature study by trying to describe an Arabic language learning platform and its use in environmental education.  From the results of the study, it was found that the Arabic learning model using The Quranic Arabic Corpus Platform can improve the proficiency of making sentences in Arabic, increase the quantity of Arabic vocabulary, and increase understanding of the position of each word in Arabic so that in short this platform makes it easier for students to learn Arabic grammar. This paper recommends that Arabic learning activities be maximized by using the Quranic Arabic Corpus platform.